Sequential Gene Expression Analysis of Coagulation Factors and Proteaseactivated Receptors in Hematopoietic Lineage Development - Kasuda, Shogo; Sakurai, Yoshihiko; Tatsumi, Kohei; Kato, Junko; Takeda, Tomohiro; Shima, Midori; Hatake, Katsuhiko (Current Angiogenesis (Discontinued), 2014)
The hematopoietic lineage is derived from pre-mesodermal cells and differentiates into hematopoietic and endothelial cells. The hematopoietic lineage cells play a key role in vasculogenesis during fetal development. Coagulation factors are essential for embryonic development and may also contribute to hematopoietic differentiation. The role of these factors and their corresponding protease-activated receptors (PARs) in the differentiation of hematopoietic lineage is not well characterized. PAR1 can be activated by activated factors VII and X as well as thrombin, and PAR4 by thrombin. We performed real-time reverse transcription PCR to assess the mRNA expression of prothrombin, tissue factor, factor V, VII, and X, and PAR1, 2, and 4 during murine-induced pluripotent stem cell differentiation into hematopoietic and hepatic lineages. PAR2 expression did not show significant changes. However, PAR1 expression increased from day 4 of hematopoietic cell differentiation. The increase was concomitant with the increase in expression of prothrombin and factor VII in the hepatic lineage from day 5–6, and with the transient upregulation of factor X in both lineages from day 7–8. PAR4 expression increased on day 4 for both lineages and peaked (>3000-fold higher than baseline level) on days 6 and 7 in hepatic and hematopoietic lineages, respectively. The increase in PAR4 levels was concomitant with an increase in prothrombin expression in hepatic lineage. These results indicate that there may be potential crosstalk between hematopoietic and hepatic lineages through a coagulation factor–PAR axis in vasculogenesis.
Keywords: real-time reverse transcription PCR